Family Planning, Population Growth and Social Welfare: A Qualitative Study - Hafid, Rachmi Nurul Hidayat (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to investigate the impact of family planning (FP) on population growth and social welfare, examining FP's multifaceted role as both a demographic intervention and a strategic tool for sustainable development. Research Method: Adopting a qualitative Systematic Literature Review (SLR) approach, this research synthesizes findings from diverse empirical studies published after 2018, focusing on FP's demographic, health, economic, and sociocultural outcomes. The review framework was structured to ensure analytical rigor and thematic coherence across selected studies. Results and Discussion: The study finds that FP significantly reduces fertility rates, improves maternal and child health, strengthens household economic stability, and promotes women's empowerment. The effectiveness of family planning (FP) programs varies across regions and is primarily influenced by sociocultural contexts, institutional capacity, and the quality of service delivery. The Demographic Transition Theory supports the role of family planning (FP) in facilitating population stabilization. The discussion highlights the importance of culturally responsive communication strategies and integrated policy frameworks in improving family planning outcomes. Implications: Practical implications include integrating family planning (FP) into education, gender equity, and public health agendas, while strengthening community engagement and equitable access to services.